Effects of Stem Cell Factor/c-Kit Signaling on In Vitro Maturation of Porcine Oocytes and Subsequent Developmental Competence After Fertilization - Kim, Eunhye; Cai, Lian; Hyun, Sang-Hwan (Frontiers in Veterinary Science, 2021)
Stem cell factor (SCF), also known as c-Kit ligand, plays an important role in the proliferation of primordial germ cells and the survival of oocytes during follicular development. The aim of this study was to investigate the effect of SCF/c-Kit signaling on in vitro maturation (IVM) of porcine oocytes by analyzing nuclear and cytoplasmic maturation, oocyte size, cumulus cell expansion, and developmental competence to the blastocyst stage. Moreover, mRNA expression patterns of porcine cumulus cells and oocytes were evaluated using qRT-PCR. Following 42 h of IVM, 10 and 50 ng/mL SCF-treated groups exhibited significantly (P < 0.05) increased polar body extrusion rates and intracellular glutathione levels compared with the control group. The cumulus expansion index significantly (P < 0.05) increased in all SCF-treated groups compared with the control samples. mRNA levels of the proapoptotic gene Bax and apoptosis-related cysteine peptidase Caspase3 were lower in SCF-treated cumulus cells than in the control group. Notably, the diameter of oocytes after IVM, the mRNA expression of well-known oocyte-secreted factors (GDF9 and BMP15), and an oocyte-specific protein essential for ovulation and oocyte health (YBX2) were significantly (P < 0.05) higher in SCF-treated than in non-treated oocytes. Inhibition of c-Kit during porcine IVM using ACK2, an antagonistic blocker of c-Kit, significantly (P < 0.05) decreased the polar body extrusion rate compared with the control, as well as blastocyst formation rate compared with the 10 ng/mL SCF-treated group. In conclusion, the effect of SCF/c-Kit-mediated signaling during porcine IVM could be ascribed to the reduced expression of apoptosis-related genes and higher expression of oocyte-specific/secreted factors.